2019
DOI: 10.1002/chem.201806432
|View full text |Cite
|
Sign up to set email alerts
|

Not Your Usual Bioisostere: Solid State Study of 3D Interactions in Cubanes

Abstract: Previous studies by Desiraju and co‐workers have implicated the acidic hydrogen atoms of cubane as a support network for hydrogen bonding groups. Herein we report a detailed structural analysis of all currently available 1,4‐disubstituted cubane structures with an emphasis on how the cubane scaffold interacts in its solid‐state environment. In this regard, the interactions between the cubane hydrogen atoms and acids, ester, halogens, ethynyl, nitrogenous groups, and other cubane scaffolds were cataloged. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The extraordinary platonic solid cubanes have intrigued chemists for decades (35)(36)(37) and are now important functional groups in a wide range of pharmaceuticals and agrochemicals (36,38). Cubanes are benzene bioisosteres with unique properties: 1) unlike benzene, cubane is biologically stable and inherently nontoxic; 2) enhanced water solubility compared to benzene due to the disruption of π stacking; and 3) formation of unusual C-H•••O hydrogen bonds caused by the strong s-character in the C-H bonds itself induced by the p-character of the C-C bonds (39,40). Synthetic and medicinal chemistry approaches for cubane function discovery can be challenging, so we considered the possibility of developing a Darwinian approach to the evolution of macromolecules functionalized by cubane bioisosteres.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The extraordinary platonic solid cubanes have intrigued chemists for decades (35)(36)(37) and are now important functional groups in a wide range of pharmaceuticals and agrochemicals (36,38). Cubanes are benzene bioisosteres with unique properties: 1) unlike benzene, cubane is biologically stable and inherently nontoxic; 2) enhanced water solubility compared to benzene due to the disruption of π stacking; and 3) formation of unusual C-H•••O hydrogen bonds caused by the strong s-character in the C-H bonds itself induced by the p-character of the C-C bonds (39,40). Synthetic and medicinal chemistry approaches for cubane function discovery can be challenging, so we considered the possibility of developing a Darwinian approach to the evolution of macromolecules functionalized by cubane bioisosteres.…”
Section: Significancementioning
confidence: 99%
“…A Unique Hydrogen Bond within the Cubane-Protein Complex Structure. Unlike phenyl or other simple arene moieties, cubane can also engage in the formation of stabilizing C−H cubane •••O bonds due to the rather high acidity of the cubyl H atoms (40). Such nonclassical hydrogen bonds also seem to occur between a dU C unit of the aptamer and a carbonyl unit of amino acids of PvLDH.…”
Section: Mechanism Of Discrimination Of Binding Recognition By Cubamer Formentioning
confidence: 99%
“…The few examples known offer a window to a fascinating structural chemistry including each of these rigid linker motifs. Previous studies by Desiraju and our research group demonstrated different modes of interaction for a variety of cubane derivatives [10e,f] . Alongside the exploration and modernization of the synthetic chemistry of scaffold hydrocarbon molecules in our laboratory [11] investigations of the supramolecular interactions of BCP derivatives offer insight into the expected intermolecular interactions engaged and promoted by this subunit.…”
Section: Introductionmentioning
confidence: 94%
“…The common feature of all supramolecular zig-zag chains is their propagation by crystallographic glide symmetry, see ESI Table 4. A representative chain in the crystal of 93 157 is shown in Fig. 10(a).…”
Section: Linear One-dimensional Supramolecular Chains Sustained By Cmentioning
confidence: 99%